A case-control study on pregnancy in Italian Cystic Fibrosis women. Data from the Italian Registry. (December 2018) - Giordani, B.; Quattrucci, S.; Amato, A.; Salvatore, M.; Padoan, R.
Abstract: Background: Pregnancy in CF women is no longer an exceptional event, but few information on its effect on clinical status in European CF patients are available. This study describes Italian CF pregnant population, to investigate its effect on CF woman. Methods: Data were collected (2010–2015) by the Italian CF Registry. A case-control study was performed between pregnant and never pregnant women. Results: A total of 81 pregnant women (aged 18-45ys) were identified with a mean age at pregnancy of 31ys. Median age at diagnosis resulted higher in cases (P = 0.010). A decline from 6 to 12 months before pregnancy to one year after delivery in BMI (P = 0.034), in FEV1 (P < 0.001) and FVC (P < 0.001) was registered among cases. Difference in change between cases and controls was found for the BMI (P = 0.006); weak evidence of difference in FEV1 (p = 0.080) and FVC (p = 0.056) were noted between the groups. Conclusion: Data from ICFR show that CF women can become mother with only slight adverse effect on their nutritional status. Further study should be carried out to investigate long term effect of pregnancy on lung function. Highlights: The mean age at pregnancy was 31ys; Decrease on nutritional status and lung function among pregnant women. Difference in median age at diagnosis: pregnant (8.1 yrs) and non-pregnant (2.0 yrs). Difference in change between cases and controls for the nutritional status.